(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
In this article, biogenic stimulants, their description and classification of biogenic stimulants. Biogenic stimulants from corpses and biogenic stimulants from mud and animals are scientifically proven.